Factors of procrastinate towards employee’s performance at Lembaga Pertubuhan Peladang Bandaraya Melaka / Noor Ainie Khamis - Khamis, Noor Ainie (Faculty of Business and Management, 2019)
Procrastinate has a negative impact on the productivity and health of individual and organization. It also known as a self-regulatory failure or delay work task. The main purpose of conducting this research paper is to examine the factor of procrastinate toward employee’s performance. Objective: to identify the relationship between time pressure and employee’s performance, to examine the relationship between work environment and employee’s performance, to study the relationship between decision making and employee’s performance and to analyse the relationship between job-related stress and employee’s performance. Methodology: the population in this study conducted at Lembaga Pertubuhan Peladang Bandaraya Melaka were 80 employees and the sample size were 66. Data collection: collect data by using questionnaires and analyses data respondent by Statical Package for Social Science (SPSS). It’s to analyses the data of descriptive, reliability, correlation and multiple regression analysis. Result: the finding shows have three independent variable significant which are time pressure, decision making and job-related stress while a work environment is not significant with employee’s performance in Lembaga Pertubuhan Peladang.